«The Book of our Father Korkut» in children’s Literature - Imperiyat A. Khalipaeva; Burkhan A. Berberov; Adam M. Gutov (Кавказология)
This article highlights some aspects of folklore education, purposeful activities to understand the ideals and values of the native people. Mastering the traditions of folk culture and folklore by children appears to be the basis for the harmonious development of the individual, the most important factor in ensuring the continuity of culture. The ideas of the great thinkers of the East have made a significant contribution to world pedagogy. Among them, a special place is given to the pedagogical ideas of the Korkut dads. And only in recent years has interest in this treasury of pedagogical thought revived. They had and still have an immense influence on ideas about man, on the formation and improvement of the theory of education and training of the younger generation. And this day is a breeding ground for the formation of ideas not only about a person and his upbringing but also about humanism, about the formation of a comprehensively developed personality. Great scientist-teachers, philosophizing about man, personality, education and training of the younger generation, attached great importance to work, knowledge, intelligence, the art of speech, and high moral qualities. They wanted to see a person comprehensively developed, skillful, and educated. Pedagogical principles, guidelines, instructions and advice, requirements and recommendations to the teachers of Korkut are still relevant and in demand today.